Abrasive Resistance, Adhesion Strength, and Corrosion Rate of ASTM A36 Steel Plate - Herman Praktino; Wimar Bhara Trisnadi; Sholihin Sholihin (Department of Ocean Engineering, 2024)
The maritime industry is one of the natural resources management industries that uses steel as its fundamental component. Much research and development have been conducted to increase the quality and life span of the steel used. ASTM A36 low-carbon steel is one of the steel variants commonly used on offshore structures because of its advantages. This research was conducted to achieve the additional effect of nano-alumina of 0%, 1,5% and 3% in the epoxy coating on adhesive strength, abrasive resistance and corrosion rate prediction. At pull-off testing, the highest adhesion strength was obtained at a mixed variation of 0% with a value of 7,7022 MPa. At the abrasion resistance test, the highest abrasion resistance was obtained at a mixed variation of 3% with a value of 16.7 grams. The lowest value of the corrosion rate prediction test was obtained on the mixed variation of 1.5% with a value of 0.005410622 mph.